Heat Transfer Characteristics of Hybrid Nanofluids Al2O3/ZnO as Working Fluid in Electronic Cooling Systems - Devia Gahana Cindi Alfian (ROTASI, 2022)
The use of nanofluid as a working fluid to improve equipment performance has been growing recently. Utilization of nanofluid hybrids is the development of mono nanofluid to improve heat transfer performance which is still not maximized when using mono nanofluid. This research was conducted to determine the performance of hybrid nanofluids with composition of Al2O3/ZnO-Distilled Water as working fluids in electronic devices. The process of making hybrid nanofluids was carried out using a two-step method using an ultrasonic cleaner for 3 hours. Furthermore, the test was carried out by varying the ratio of Al2O3 and ZnO nanoparticles at 25%:75%, 50%:50%, 75%:25% at exactly 0.5% volume fraction. Based on the test results, adding nanoparticles can increase the heat transfer in the working fluid. The use of nanofluid hybrids at varying ratios of Al2O3:ZnO (50%:50%) with a flow rate of 0.7 L/min has the highest heat transfer coefficient value of 220.14 W/m2.oC at Reynolds Number 178.4 and requires pumping power of 0.649 W. Moreover, distilled water with a flow rate of 0.7 L/min has the heat transfer coefficient of 77.48 W/m2.oC at Reynolds Number 130.1 and requires a pump power of 0.425 W.